Treatment of primary hyperhidrosis with oral anticholinergic medications: a systematic review. (21st February 2017) - Cruddas, L.; Baker, D.M.
Abstract: Primary hyperhidrosis is a condition characterized by excessive sweating. Patients are treated off‐license with oral anticholinergic medications and report adverse events associated with systemic anticholinergic interactions. This review assesses clinical evidence of efficacy, impact on quality of life and adverse events associated with oral anticholinergic therapy for primary hyperhidrosis. PRISMA guidelines were implemented to complete a systematic review (PROSPERO:CRD42016036326). MEDLINE, EMBASE and PubMed were searched from 1946 to 2015. Inclusion criteria included observational and experimental studies, anticholinergic medication use in primary hyperhidrosis, oral therapy and clear diagnostic and outcome measures. Twenty‐three articles relevant to the inclusion criteria were analysed. Oxybutynin therapy improved symptoms in an average of 76.2% (range 60–97%) patients and improved QOL in 75.6% (range 57.6–100%) of patients. Methantheline bromide therapy was associated with a 41% reduction in axillary sweating, 16.4% reduction in palmar sweating, 25% decrease in HDSS score and 40.9% increase in DLQI score. Outcome measures of glycopyrrolate therapy were too variable to collate. Dry mouth was reported in 73.4% (range 43.3–100%) of participants taking oxybutynin 10 mg/day, 38.6% (range 27.8–63.2%) of patients taking glycopyrrolate and 68.8% of patients taking methantheline bromide. Nine studies reported that patients stopped therapy due to adverse events. In eight of these studies, a mean of 10.9% of total participants ceased treatment due to dry mouth. Evidence of oral anticholinergic therapy for hyperhidrosis is limited. However, its use is associated with improvement in quality of life and clinical symptoms but at the cost of considerable adverse events.